2017
DOI: 10.1038/srep42483
|View full text |Cite
|
Sign up to set email alerts
|

The secondary resistome of multidrug-resistant Klebsiella pneumoniae

Abstract: Klebsiella pneumoniae causes severe lung and bloodstream infections that are difficult to treat due to multidrug resistance. We hypothesized that antimicrobial resistance can be reversed by targeting chromosomal non-essential genes that are not responsible for acquired resistance but essential for resistant bacteria under therapeutic concentrations of antimicrobials. Conditional essentiality of individual genes to antimicrobial resistance was evaluated in an epidemic multidrug-resistant clone of K. pneumoniae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
86
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(101 citation statements)
references
References 54 publications
11
86
0
Order By: Relevance
“… 16 The additional loci identified in the present study included dedA , which encodes a putative integral membrane protein; the previous study had demonstrated that dedA is essential for growth during exposure to colistin. 32 usg was also identified by a transposon insertion in the present study; notably, usg is located upstream of dedA in the K. pneumoniae genome, so insertion at usg may have polar effects on dedA expression. Multiple additional loci associated with colistin resistance were also identified for the first time in the present study.…”
Section: Discussionsupporting
confidence: 56%
“… 16 The additional loci identified in the present study included dedA , which encodes a putative integral membrane protein; the previous study had demonstrated that dedA is essential for growth during exposure to colistin. 32 usg was also identified by a transposon insertion in the present study; notably, usg is located upstream of dedA in the K. pneumoniae genome, so insertion at usg may have polar effects on dedA expression. Multiple additional loci associated with colistin resistance were also identified for the first time in the present study.…”
Section: Discussionsupporting
confidence: 56%
“…To answer this question, we performed transposon (Tn)-directed insertion sequencing (TraDIS) using the clinical bloodstream isolate ID40, which is resistant to many ␤-lactam antibiotics, to assess the resistome of P. aeruginosa by an approach similar to that described by Jana et al (17). TraDIS has been shown to be a valuable tool under particular conditions and in various approaches to find genes responsible for growth (18)(19)(20)(21).…”
mentioning
confidence: 99%
“…ATCC reference strains included Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, and Acinetobacter baumannii. MDR strains E. coli ST131 and K. pneumoniae ST258 are clinical isolates from urinary tract [7] and wound infections [8], respectively. A panel of β-lactamase resistant clinical isolates of were provided by Laurent Poirel.…”
Section: Media Antibiotics Bacterial Strains and Peptide Synthesismentioning
confidence: 99%